Corilagin alleviates intestinal ischemia/reperfusion injury by relieving oxidative stress and apoptosis via AMPK/Sirt1-autophagy pathway. Issue 4 (February 2023) - Li, Bin; Li, Wenlian; Zheng, Meiling; Wang, Yunxiang; Diao, Yunpeng; Mou, Xiaojuan; Liu, Jing
Intestinal ischemia/reperfusion (II/R) injury is a common pathological process with high clinical morbidity and mortality. Autophagy plays an important role in the pathological development of II/R. Corilagin (CA) is a natural ellagitannin with various pharmacological effects such as autophagy regulation, antioxidant, and antiapoptosis. However, whether CA alleviates II/R injury is still unclear. In this study, we had found that CA significantly attenuated II/R induced intestinal tissue pathological damage, oxidative stress, and cell apoptosis in rats. Further studies showed that CA significantly promoted AMPK phosphorylation and sirt1 expression, and thus activated autophagy by upregulating protein expression of autophagy-related proteins Beclin1 and LC3II and promoting SQSTM1/P62 degradation both in vivo and in vitro . Inhibition of AMPK phosphorylation by its inhibitor compound C(CC) significantly abolished CA-mediated autophagy activation and the relievable effects on oxidative stress and apoptosis in vitro, suggesting the excellent protective activity of CA against II/R injury via AMPK/Sirt1-autophagy pathway. These findings confirmed the potent effects of CA against II/R injury, and provided novel insights into the mechanisms of the compound as a potential candidate for the treatment of II/R.